2018
DOI: 10.1265/jjh.73.178
|View full text |Cite
|
Sign up to set email alerts
|

Historical Transition of Sexuality Education in Japan and Outline of Reproductive Health/Rights

Abstract: In this paper, we describe the historical transition of sexuality education in Japan and the direction of sexuality education taken by the Ministry of Education, Culture, Sports, Science and Technology (MEXT). Reproductive health/rights, a key concept in sex education, is also discussed. In Japanese society, discussion on sexuality has long been considered taboo. After the Second World War, sexuality education in Japan began as "purity education." From 1960 until the early 1970s, physical aspects such as genit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…According to the latest survey carried out every 2 years by the Japan Family Planning Association, only 50% of women and 40% of men in 2017 were aware of the available emergency contraceptive methods . In Japan, no specific actions leading to pregnancy, or information on contraceptive and emergency contraceptive methods, are included in the compulsory sex education curriculum . Indeed, the present results showed that over 70% of women learned about emergency contraceptive methods via the internet or friends, compared with less than 6% at school.…”
Section: Discussionmentioning
confidence: 58%
“…According to the latest survey carried out every 2 years by the Japan Family Planning Association, only 50% of women and 40% of men in 2017 were aware of the available emergency contraceptive methods . In Japan, no specific actions leading to pregnancy, or information on contraceptive and emergency contraceptive methods, are included in the compulsory sex education curriculum . Indeed, the present results showed that over 70% of women learned about emergency contraceptive methods via the internet or friends, compared with less than 6% at school.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, it is not clear whether this difference that was found was due to the type of pharmacy program undertaken and its curriculum, or the younger age of the participants who had graduated from the 6-year program. Sex education received in primary and secondary schools differs with age; therefore, the age of participants could affect the inclination to provide SRH services [28]. It is also important to consider that sex education provided in Japan may not be adequate and needs improvement [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is a woman’s fundamental human right to choose and determine (the right to self-determination) whether to marry, whether to have children, when to have children, how many children to have, and how much of a gap to leave between each child. To consider and come to a decision on this, women need accurate information [7]. Fertility depends on age and begins to decline earlier in women than in men.…”
Section: Proactive Education On Reproductive Healthmentioning
confidence: 99%